HAK DAN KEWAJIBAN SUAMI ISTRI DALAM PERNIKAHAN - Muda’i, Syaiful; Rohman Wahid, Abdur (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2023)
In married life, everyone desires and aspires to have a prosperous and happylife, full of love, harmony and even being able to achieve all their goals anddreams. Husbands love their wives, wives love and respect their husbands.Children respect and obey their parents and in turn both parents areresponsible, provide for all their needs and protect them. It's truly a miniaturelife that every person dreams of. Therefore, many figures and public figuressay and quite a few of the realities of life also state that wealth and wealth arenot the key to happiness and are not everything. A family is said to be happy ifthe rights of husband and wife are fulfilled. The fulfillment of two basic needs,namely physical needs and spiritual needs of each husband and wife. Includingphysical life is clothing, food, health and education. Meanwhile, spiritual needsinclude fulfilling both religious and other scientific education.